L'éruption patriote: The Revolt against Dalhousie and the Petitioning Explosion in Nineteenth-Century French Canada. Issue 3 (2019) - Carpenter, Daniel; Brossard, Doris
Abstract : As much as any other site in the nineteenth century, Francophone Lower Canada saw immense waves of popular petitioning, with petitions against British colonial administration attracting tens of thousands of signatures in the 1820s. The petition against Governor Dalhousie of 1827–28 attracted more than 87, 000 names, making it one of the largest mass petitions of the Atlantic world on a per-capita scale for its time. We draw upon new archival evidence that shows the force of local organization in the petition mobilization, and combine this with statistical analyses of a new sample of 1, 864 names from the anti-Dalhousie signatory list. We conclude that the Lower Canadian petitioning surge stemmed from emergent linguistic nationalism, expectations of parliamentary democracy, and the mobilization and alliance-building efforts of Patriote leaders in the French-Canadian republican movement. As elsewhere in the nineteenth-century Atlantic, the anti-Dalhousie effort shows social movements harnessing petitions to recruit, mobilize, and build cross-cultural alliances.